2018
DOI: 10.5603/kp.a2017.0185
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of N-terminal-pro B-type natriuretic peptide as a heart failure marker in patients undergoing percutaneous left atrial appendage occlusion

Abstract: When diagnosing HF in atrial fibrillation patients, the higher cut-off value of NT-proBNP should be used. NT-proBNP remains an appropriate diagnostic marker of HF in patients after LAAO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The evolution of surgical techniques toward preserving the right atrial appendage has led to a reduction in the incidence of postoperative pulmonary edema [45]. Two small studies indicated a slight rise in brain natriuretic peptide levels after transcatheter LAAO (32 patients together) [47,48]. On the other hand, there are several studies demonstrating that LAAO does not lead to any significant changes in natriuretic peptide levels at all [43,[49][50][51][52].…”
Section: Collateral Impact Of Laa Lossmentioning
confidence: 99%
“…The evolution of surgical techniques toward preserving the right atrial appendage has led to a reduction in the incidence of postoperative pulmonary edema [45]. Two small studies indicated a slight rise in brain natriuretic peptide levels after transcatheter LAAO (32 patients together) [47,48]. On the other hand, there are several studies demonstrating that LAAO does not lead to any significant changes in natriuretic peptide levels at all [43,[49][50][51][52].…”
Section: Collateral Impact Of Laa Lossmentioning
confidence: 99%